Wildcat Capital Investors : real estate private equity - Furfine, Craig (London : SAGE Publications Ltd, 2017)
Wildcat Capital Investors is a small real estate private equity company. Its MBA intern, Jessica Zaski, is asked to develop a financial model for the purchase of Financial Commons, a 90,000 square foot office building in suburban Chicago. By simple metrics, the property seems to be a good value, but with credit conditions tight, Jessica must consider whether outside investors would be comfortable with the risks of investing in the midst of a severe commercial real estate downturn. Wildcat is designed to give students exposure to both the quantitative and qualitative aspects of investing in commercial real estate through a private equity structure. Beyond the numbers, the case allows for a discussion of the process of finding suitable real estate investments. The importance of the simultaneous negotiations that Wildcat must have with the seller, the lender, and the outside investor can be emphasized.
Originally published: Furfine, C., (2011). Wildcat Capital Investors : real estate private equity. (case revised 11/02/2015; teaching notes revised 01/02/2012). 5-310-510. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wildcat Capital Investors; Real estate investment -- United States -- Case studies; Commercial real estate -- United States -- Case studies; Residential real estate -- United States -- Case studies; Private equity -- United States -- Case studies; Real estate business -- United States -- Case studies